HEMOPHAGOCYTIC SYNDROME SECONDARY TO ANTICONVULSANT-RELATED DRESS SYNDROME: A CASE REPORT - de Melo, Caroline Cristina; Albanese, Bianca Vieira; Borges, Lucas Ferreira; Silva, Ana Luara Barcelos; Maronese, Francesco Carlo; Granado Júnior, Marcos Donisete (Seven Editora, 2025)
DRESS (Drug Reaction with Eosinophilia and Systemic Inflammation) is a serious adverse reaction that can present with significant multivisceral involvement. The exacerbated immune activation that occurs in DRESS syndrome can trigger hemophagocytic syndrome, generating intense systemic inflammation with unfavorable and potentially fatal clinical evolution. The association between hemophagocytic syndrome and DRESS is rare; however, early recognition of signs and symptoms is fundamental for timely diagnosis and treatment, reducing the likelihood of adverse outcomes and increasing the chances of therapeutic success. DOI: https://doi.org/10.56238/sevened2025.037-038